Use of Capillary Electrophoresis Method in Determination of Quantitative Content of Mangiferin in Grass of Species of Genus Hedysarum (Hedysarum Caucasicum M.Bieb., Hedysarum Grandiflorum Pall., Hedysarum Daghestanicum Rupr. ex Boiss) of flora of the North Caucasus - D. R. Imachueva; F. K. Serebryanaya (Разработка и регистрация лекарственных средств, 2021)
Introduction. The species of the genus Hedysarum L. of the Fabaceae family are of significant interest in connection with the accumulation of a group of biologically active substances with antibacterial and antiviral activity against DNA-containing viruses.Aim. The purpose of the work is to develop a method for the quantitative determination of mangiferin in the aboveground part of species of the genus Hedysarum L., Hedysarum caucasicum M.Bieb., Hedysarum grandiflorum Pall., Hedysarum daghestanicum Rupr. ex. Boiss. collected in the North Caucasus by zonal capillary electrophoresis.Materials and methods. The objects of the study were species of the genus Hedysarum L., namely Hedysarum caucasicum M.Bieb., Hedysarum grandiflorum Pall., Hedysarum daghestanicum Rupr. ex. Boiss. collected in the North Caucasus. Registration of electronic spectra was carried out on capillary electrophoresis "KAPEL'®-105m" (OJSC "Lumex-marketing", Russia) with quartz capillary Leff./Ltol. = 50/60 cm, ID = 75 μm. As a standard sample, mangiferin (substance-powder, mangiferin content ≥98 %, Sigma-Aldrich, Lot SLBP4044V) was used.Results and discussion. As a result of comprehensive pharmacognostic studies of species of the kopecki genus growing in the North Caucasus under natural conditions, as well as under the conditions of introduction on the territory of the Botanical Garden of the Pyatigorsk Medical and Pharmaceutical Institute and the Mountain Botanical Garden of the Dagestan Federal Research Center of the Russian Academy of Sciences, we developed a method for the isolation and quantitative determination of mangiferin by capillary electrophoresis.Conclusion. Studies show that the use of the zonal capillary electrophoresis method in the analysis of xanthones, including the determination of the quantitative content of mangiferin, is promising. The largest content of mangiferin (0.25 %) is distinguished by Hedysarum caucasicum M.Bieb., which confirms the assumption based on molecular genetic studies, since it is this species that belongs to the Obscura section, as well as the alpine penny used to produce mangiferin. Therefore, it is possible to provide this technique for analysis of mangiferin xanthone glycoside along with spectrophotometry and high performance liquid chromatography.